2018
DOI: 10.3390/nu10050550
|View full text |Cite
|
Sign up to set email alerts
|

Daily Intake of Milk Powder and Risk of Celiac Disease in Early Childhood: A Nested Case-Control Study

Abstract: Milk powder and gluten are common components in Swedish infants’ diets. Whereas large intakes of gluten early in life increases the risk of celiac disease in genetically at-risk Swedish children, no study has yet evaluated if intake of milk powder by 2 years of age is associated with celiac disease. A 1-to-3 nested case-control study, comprised of 207 celiac disease children and 621 controls matched for sex, birth year, and HLA genotype, was performed on a birth cohort of HLA-DR3-DQ2 and/or DR4-DQ8-positive ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Likewise, the aOR for the milk quantity variable provides no support for the authors’ preliminary hypothesis that increased consumption of cow’s milk may increase CD risk. A recent study that examined the impact of the quantity of powdered milk consumed on subsequent CD diagnosis in young children in Sweden found no association between quantity of powdered milk consumed and CD 116. Thus, while the studies are different with respect to the specifics, the result for the fluid milk quantity variable in the present study is consistent with the findings on powdered milk from this recent Swedish study.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, the aOR for the milk quantity variable provides no support for the authors’ preliminary hypothesis that increased consumption of cow’s milk may increase CD risk. A recent study that examined the impact of the quantity of powdered milk consumed on subsequent CD diagnosis in young children in Sweden found no association between quantity of powdered milk consumed and CD 116. Thus, while the studies are different with respect to the specifics, the result for the fluid milk quantity variable in the present study is consistent with the findings on powdered milk from this recent Swedish study.…”
Section: Discussionsupporting
confidence: 87%
“…The dietary pattern at age 9 mo associated with the lower risk of CDA was characterized by lower intakes of both Human milk as well as Infant formula. However, neither human milk nor formula type has previously been associated with celiac disease [ [35] , [36] , [37] ]. Some food groups were included in dietary patterns with conflicting associations with the study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 , 22 A case-control study on milk powder consumption during the first two years of life in genetically susceptible children for CD showed that milk powder intake was not associated with CD in Swedish children. 24 Another case-control research found that CD was not statistically associated with the duration of breastfeeding, but was associated with skim milk consumption. 19 A randomized controlled trial showed that avoiding cow’s milk- based formula for infants at risk for CD does not reduce the development of disease.…”
Section: Discussionmentioning
confidence: 99%